Preparation method of iron-silicon-titanium doped iron-silicon-aluminum soft magnetic powder core

By doping iron-silicon titanium powder and heat treatment and pressing, the comprehensive magnetoelectric performance of crushed iron-silicon aluminum soft magnetic powder core is improved, and the problems of high cost and performance choices in the existing technology are solved, and efficient DC bias performance is achieved. and low loss performance.

CN119446767APending Publication Date: 2025-02-14YANGZHOU LEADING INNOVATION MATERIALS TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411819048.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

When improving DC bias performance and loss performance, the existing ferrosilicon aluminum soft magnetic powder cores are costly and difficult to comprehensively improve comprehensive performance. They usually need to make a choice between DC bias performance and loss performance.

Method used

By doping ferrosilicon titanium powder, the comprehensive magnetoelectric performance of broken ferrosilicon aluminum is improved. The specific steps include heat treatment of ferrosilicon titanium soft magnetic powder, screening the particle size of crushed ferrosilicon aluminum powder, doping proportionally with ferrosilicon titanium powder and crushing ferrosilicon aluminum powder, and pressing and heat treatment under the protection of inert gas, and finally Surface spray-insulating coating.

Benefits of technology

The 60μ iron silicon titanium doped iron silicon aluminum soft magnetic powder core prepared has a DC bias performance of no less than 55% under 100Oe conditions, and a volume loss Pcv under 50kHz and 100mT conditions is less than 220mW/cm3, which is significantly better than Properties of conventional crushed ferrosilicon aluminum powder core.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005182638490000041
    Figure BDA0005182638490000041
Patent Text Reader

Abstract

The invention discloses a preparation method of an iron-silicon-titanium doped iron-silicon-aluminum soft magnetic powder core, which comprises the following steps: placing iron-silicon-titanium powder in an air atmosphere for heat treatment, selecting broken iron-silicon-aluminum powder subjected to insulation coating, carrying out particle size screening, and doping with the iron-silicon-titanium powder in proportion to prepare the iron-silicon-titanium doped iron-silicon-aluminum soft magnetic powder core. By controlling the heat treatment temperature and time, uniform oxidation insulation modification on the surface of the powder can be realized. Furthermore, on the basis of not changing the original insulation powder technology, the comprehensive magnetoelectric performance of the crushed Fe-Si-Al can be obviously improved by regulating and controlling the doping proportion, forming parameters and magnetic core heat treatment parameters of the Fe-Si-Ti powder subjected to heat treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of soft magnetic materials, and in particular relates to a method for preparing an iron silicon titanium doped iron silicon aluminum soft magnetic powder core. Background Art

[0002] The composition of FeSiAl alloy is Fe-9.6wt%Si-5.4wt%Al, and its saturation magnetic induction intensity can reach about 1.05T, and the alloy magnetic permeability is as high as 120000. FeSiAl alloy is easy to be crushed into powder, and the effective magnetic permeability of the prepared FeSiAl powder core ranges from 26 to 125. It has the characteristics of low loss, low magnetostriction coefficient and low magnetocrystalline anisotropy constant, and is widely used in anti-electromagnetic interference inductors, filter inductors and line filters.

[0003] Patent CN113470916B designed a phosphate-silane-silicon-containing aromatic resin three-layer coating structure to insulate and coat the aerosolized iron silicon aluminum magnetic powder, and prepared an aerosolized iron silicon aluminum soft magnetic powder core with a magnetic permeability of 66. The DC bias performance under 100Oe is higher than 55%, and the volume loss under 50kHz and 100mT is lower than 170mW / cm 3 Patent CN117790102A discloses a method for manufacturing a high DC biased sendust powder core. First, the fine alloy powder is heat treated in a vacuum or nitrogen environment. Then, the surface of the crushed sendust powder is insulated and coated with an aqueous solution of aluminum dihydrogen phosphate and a hybrid coating agent. The prepared 60μ powder core has a DC bias performance of more than 70% under 100Oe conditions. However, the loss performance of the powder core has deteriorated significantly, with a volume loss of up to 341mW / cm at 50kHz and 100mT. 3 .

[0004] Compared with crushed Sendust, atomized Sendust can significantly improve DC bias performance and loss performance by improving powder preparation technology, but it also brings about a significant increase in the cost of soft magnetic powder. At present, the cost of atomized Sendust powder is more than 20% higher than that of crushed powder. It is difficult to comprehensively improve the comprehensive performance of magnetic powder cores by simply improving the coating technology of crushed Sendust powder cores. Usually, a trade-off is made between DC bias performance and loss performance based on actual performance requirements. Summary of the invention

[0005] In view of the current technical status and market demand, the present invention provides a method for preparing an iron silicon titanium doped iron silicon aluminum soft magnetic powder core. On the basis of not changing the original insulating powder technology, the comprehensive magnetic and electrical properties of the crushed iron silicon aluminum are improved by doping iron silicon titanium powder. Compared with materials such as iron silicon and iron nickel, iron silicon titanium materials have excellent characteristics such as high strength, corrosion resistance, and low loss, and the material cost is significantly lower than that of materials such as iron nickel, so it is more conducive to later market application and promotion.

[0006] The method for preparing the FeSiTi-doped FeSiAl soft magnetic powder core of the present invention comprises the following steps:

[0007] Step 1: heat treating the iron silicon titanium soft magnetic powder in an air atmosphere;

[0008] Step 2: Sieve the broken iron-silicon-aluminum powder after insulation coating with a 300-mesh sieve, and take the powder with a particle size greater than 300 mesh;

[0009] Step 3: Mix the iron silicon titanium powder and the crushed iron silicon aluminum powder obtained in step 1 and step 2 according to a proportion, then add a release agent, mix well, and obtain the magnetic powder to be formed;

[0010] Step 4: Using a press machine, press the magnetic powder to be formed prepared in step 3 into a powder core blank;

[0011] Step 5: Under the protection of inert gas, the powder core blank pressed in step 4 is kept at 680° C. to 750° C. to obtain a semi-finished magnetic powder core;

[0012] Step 6: Spray a layer of insulating, high temperature resistant epoxy resin coating onto the surface of the semi-finished magnetic powder core obtained in step 5 to obtain a finished metal soft magnetic powder core.

[0013] In step 1, the original powder particle size of the iron silicon titanium magnetic powder is ≤300 mesh, and its composition by mass percentage is: Si 4.5% to 6.5%, Ti 0.5% to 2.0%, and the rest is Fe.

[0014] In step 1, the air atmosphere heat treatment temperature is 300° C. to 450° C., and the heat preservation time is 20 minutes to 90 minutes.

[0015] In step 2, the magnetic permeability of the selected crushed sendustine powder after insulation coating is 50-75.

[0016] In step 3, the mass of the iron silicon titanium powder accounts for 20% to 40% of the total mass of the powder after doping.

[0017] In step 4, the pressing pressure is 1700MPa to 2200MPa.

[0018] In step 5, the insulation time is 110 minutes to 160 minutes.

[0019] The present invention prepares a 60μ FeSiTi doped FeSiAl soft magnetic powder core, the DC bias performance under 100Oe is not less than 55%, and the volume loss Pcv under 50kHz and 100mT is less than 220mW / cm 3 .

[0020] The present invention uses iron silicon titanium soft magnetic powder, which has excellent characteristics of low loss and corrosion resistance. First, the iron silicon titanium powder is pretreated in an air atmosphere, and by controlling the heat treatment temperature and time, uniform oxidation insulation modification of the powder surface can be achieved. Furthermore, on the basis of not changing the original insulating powder technology, by adjusting the doping ratio, molding parameters and heat treatment parameters of the iron silicon titanium powder after heat treatment, the comprehensive magnetic and electric properties of the crushed iron silicon aluminum can be significantly improved. The scheme of the present invention is easy to operate and is conducive to subsequent market application and promotion. DETAILED DESCRIPTION

[0021] The present invention is further described below in conjunction with the examples. The described examples and their results are only used to illustrate the present invention, and should not and will not limit the present invention described in detail in the claims.

[0022] Embodiment 1:

[0023] 200.0 g of 300-mesh iron silicon titanium magnetic powder is selected and heat-treated for 90 minutes at 450° C. in an air atmosphere to obtain a pretreated powder; crushed iron silicon aluminum powder with a magnetic permeability of 75 μ after insulation coating is taken, sieved with a 300-mesh sieve, and 800.0 g of powder with a particle size greater than 300 mesh is taken; the pretreated iron silicon titanium powder and the crushed iron silicon aluminum powder are mixed, and a release agent is added, and stirred evenly to obtain a powder to be formed; the uniformly mixed magnetic powder to be formed is pressed into a powder core blank at a pressing pressure of 1700 MPa; the pressed powder core blank is kept at 680° C. for 160 minutes in an inert gas atmosphere to obtain a semi-finished magnetic powder core; finally, a layer of insulating coating is sprayed on the surface of the semi-finished magnetic powder to obtain a finished metal soft magnetic powder core.

[0024] Embodiment 2:

[0025] 250.0 g of 300-mesh iron silicon titanium magnetic powder is selected and heat-treated for 75 minutes at 435° C. in an air atmosphere to obtain a pretreated powder; crushed iron silicon aluminum powder with a magnetic permeability of 75 μ after insulation coating is taken, sieved with a 300-mesh sieve, and 750.0 g of powder with a particle size greater than 300 mesh is taken; the pretreated iron silicon titanium powder and the crushed iron silicon aluminum powder are mixed, and a release agent is added, and stirred evenly to obtain a powder to be formed; the uniformly mixed magnetic powder to be formed is pressed into a powder core blank at a pressing pressure of 1800 MPa; the pressed powder core blank is kept at 700° C. for 140 minutes in an inert gas atmosphere to obtain a semi-finished magnetic powder core; finally, a layer of insulating coating is sprayed on the surface of the semi-finished magnetic powder to obtain a finished metal soft magnetic powder core.

[0026] Embodiment 3:

[0027] 300.0 g of 300-mesh iron silicon titanium magnetic powder is selected and heat-treated for 60 minutes at 400° C. in an air atmosphere to obtain a pretreated powder; crushed iron silicon aluminum powder with a magnetic permeability of 60 μ after insulation coating is taken, sieved with a 300-mesh sieve, and 700.0 g of powder with a particle size greater than 300 mesh is taken; the pretreated iron silicon titanium powder and the crushed iron silicon aluminum powder are mixed, and a release agent is added, and stirred evenly to obtain a powder to be formed; the uniformly mixed magnetic powder to be formed is pressed into a powder core blank at a pressing pressure of 1950 MPa; the pressed powder core blank is kept at 715° C. for 130 minutes in an inert gas atmosphere to obtain a semi-finished magnetic powder core; finally, a layer of insulating coating is sprayed on the surface of the semi-finished magnetic powder to obtain a finished metal soft magnetic powder core.

[0028] Embodiment 4:

[0029] 350.0 g of 300-mesh iron silicon titanium magnetic powder is selected and heat-treated for 75 minutes at 345° C. in an air atmosphere to obtain a pretreated powder; crushed iron silicon aluminum powder with a magnetic permeability of 60 μ after insulation coating is taken, sieved with a 300-mesh sieve, and 650.0 g of powder with a particle size greater than 300 mesh is taken; the pretreated iron silicon titanium powder and the crushed iron silicon aluminum powder are mixed, and a release agent is added and stirred evenly to obtain a powder to be formed; the evenly mixed magnetic powder to be formed is pressed into a powder core blank at a pressing pressure of 2100 MPa; the pressed powder core blank is kept at 720° C. for 120 minutes in an inert gas atmosphere to obtain a semi-finished magnetic powder core; finally, a layer of insulating coating is sprayed on the surface of the semi-finished magnetic powder to obtain a finished metal soft magnetic powder core.

[0030] Embodiment 5:

[0031] 400.0 g of 300-mesh iron silicon titanium magnetic powder is selected and heat-treated for 20 minutes at 300° C. in an air atmosphere to obtain a pretreated powder; crushed iron silicon aluminum powder with a magnetic permeability of 50 μ after insulation coating is taken, sieved with a 300-mesh sieve, and 600.0 g of powder with a particle size greater than 300 mesh is taken; the pretreated iron silicon titanium powder and the crushed iron silicon aluminum powder are mixed, and a release agent is added, and stirred evenly to obtain a powder to be formed; the evenly mixed magnetic powder to be formed is pressed into a powder core blank at a pressing pressure of 2200 MPa; the pressed powder core blank is kept at 750° C. for 110 minutes in an inert gas atmosphere to obtain a semi-finished magnetic powder core; finally, a layer of insulating coating is sprayed on the surface of the semi-finished magnetic powder to obtain a finished metal soft magnetic powder core.

[0032] The pressed blank in the above embodiment is an annular powder core with an outer diameter of 27.00 mm, an inner diameter of 14.80 mm, and a height of 11.18 mm. The magnetic and electrical properties of the finished powder core are shown in the following table, wherein the diameter of the enameled wire used for the test is Φ1.00 mm, the length is 0.9 m, and the number of winding turns is 25.

[0033]

[0034] According to the size of the powder core magnetic ring, the number of winding turns, and the magnetic permeability, it can be calculated that the inductance value corresponding to the magnetic permeability of 60μ is 46.88μH, and the actual control inductance error is -8% to 8%. In the embodiment, the iron silicon titanium powder is heat-treated in an air atmosphere, and its powder surface can be oxidized to achieve surface insulation; when doped into the crushed iron silicon aluminum powder, the eddy current circuit between the iron silicon titanium powder and the iron silicon aluminum powder particles can be effectively blocked, thereby reducing the powder core loss value. By regulating the heat treatment temperature and heat treatment time in an air atmosphere, the magnetic permeability of the iron silicon titanium powder can be effectively adjusted. According to the magnetic permeability parameters of the crushed iron silicon aluminum powder, the doping ratio of the iron silicon titanium powder is adjusted to prepare an iron silicon aluminum powder core doped with iron silicon titanium with a magnetic permeability of 60μ. It can be seen from the inductance value data in the table that the inductance values ​​of the powder cores prepared in the embodiment are all within the inductance value range corresponding to 60μ.

[0035] In the present invention, firstly, 300 mesh FeSiTi powder is selected for pretreatment, then the powder below 300 mesh in FeSiAl powder is screened out, and the particle size ratio and powder doping are carried out to achieve the replacement of FeSiTi powder with the powder of the same particle size in FeSiAl powder. It can be seen from the test data that under 100Oe conditions, the DC bias performance of the doped powder core is higher than 55%, and can reach up to 61.01%; under 50kHz and 100mT conditions, the volume loss Pcv of the doped powder core is lower than 220mW / cm 3 .

[0036] By comparing the magnetic and electrical properties, it can be found that the FeSiTi doped FeSiAl soft magnetic powder core prepared by the scheme of the present invention is significantly better than the conventional crushed FeSiAl powder core, and while improving the DC bias performance, it further optimizes and improves the loss performance of the powder core. The technical scheme of the present invention is easy to operate, does not change the insulation coating technical scheme of the original powder material, and has broad market application and promotion prospects.

Claims

1. A method for preparing a FeSiTi-doped FeSiAl soft magnetic powder core, characterized in that: The iron silicon titanium powder is placed in an air atmosphere for heat treatment, and the broken iron silicon aluminum powder after insulation coating is selected, and after particle size screening, it is mixed with the iron silicon titanium powder in proportion to prepare the iron silicon titanium doped iron silicon aluminum soft magnetic powder core.

2. The preparation method according to claim 1, characterized in that The steps include: Step 1: heat treating the iron silicon titanium soft magnetic powder in an air atmosphere; Step 2: Sieve the broken iron-silicon-aluminum powder after insulation coating with a 300-mesh sieve; Step 3: Mix the iron silicon titanium powder obtained in step 1 and the crushed iron silicon aluminum powder obtained in step 2 according to a certain proportion, then add a release agent, mix well, and obtain magnetic powder to be formed; Step 4: Using a press machine, press the magnetic powder to be formed prepared in step 3 into a powder core blank; Step 5: Under the protection of inert gas, the powder core blank pressed in step 4 is kept at 680° C. to 750° C. to obtain a semi-finished magnetic powder core; Step 6: Spray a layer of insulating, high temperature resistant epoxy resin coating onto the surface of the semi-finished magnetic powder core obtained in step 5 to obtain a finished metal soft magnetic powder core.

3. The preparation method according to claim 2, characterized in that: In step 1, the original powder particle size of the iron silicon titanium magnetic powder is ≤300 mesh, and its composition by mass percentage is: Si 4.5% to 6.5%, Ti 0.5% to 2.0%, and the rest is Fe.

4. The preparation method according to claim 2, characterized in that: In step 1, the air atmosphere heat treatment temperature is 300° C. to 450° C., and the heat preservation time is 20 minutes to 90 minutes.

5. The preparation method according to claim 2, characterized in that: In step 2, the magnetic permeability of the selected crushed sendustine powder after insulation coating is 50-75.

6. The preparation method according to claim 2, characterized in that: In step 3, the mass of the iron silicon titanium powder accounts for 20% to 40% of the total mass of the powder after doping.

7. The preparation method according to claim 2, characterized in that: In step 4, the pressing pressure is 1700MPa to 2200MPa.

8. The preparation method according to claim 2, characterized in that: In step 5, the insulation time is 110 minutes to 160 minutes.

Citation Information

Patent Citations

  • Sendust soft magnetic powder core and preparation method thereof

    CN113470916B

  • Manufacturing method of high-direct-current bias iron-silicon-aluminum powder core

    CN117790102A